A successful treatment of rhinocerebral mucormycosis due to Rhizopus oryzae - Rasoul Mohammadi (Journal of Research in Medical Sciences, 2014)
Mucormycosis is an invasive fungal infection caused by filamentous fungi of the Mucoraceae family. The genera most commonly responsible are Mucor or Rhizopus. The disease occurs mostly in association with diabetic ketoacidosis. Mucormycosis has an extremely high death rate even when aggressive surgery is done. Death rates range from 25-85% depending on the body area involved. A case of rhinocerebral mucormycosis in a 65-year-old diabetic male patient typically presenting as headache, especially in parietal and frontal lobes, with nose and left eye discharge. After clinical and laboratory examination, mucormycosis was diagnosed, and Rhizopus oryzae was isolated. Systemic therapy with amphotericin B administered intravenously then replaced by posaconazole by a combination of aggressive surgery. The patient was treated and followed up for one year. We emphasize the importance of early detection and aggressive treatment in the management of this fatal disease.